Tobacco Control Research from the Perspective of Health Communication in the Digital-Intelligent Era: Literature Review of the 3rd Session of MHM2025 - ling, Jianan (The Journal of Medicine, Humanity and Media, 2025)
This literature review synthesizes five studies exploring tobacco control communication in the digital-intelligent era, focusing on health communication perspectives. The studies investigate multiple dimensions of tobacco control, including influencing factors of first smoking behavior (e.g., individual cognition, media symbols, family and social environments), effectiveness of anti-smoking public service ads (highlighting features like real cases and disease frameworks, and regional differences in acceptance), tobacco control information dissemination on social media (e.g., divergent spread of WeChat Official Account articles, key factors in high-engagement content), and the effectiveness of e-cigarette policies (noting limited outcomes due to regulatory fragmentation and conflicts in regulatory roles). Employing mixed methods—qualitative approaches (in-depth interviews, focus groups) and quantitative techniques (Python data crawling, SPSS analysis, sentiment modelling, LDA topic modeling)—alongside theoretical frameworks such as grounded theory and strategy-tactics theory, these studies reveal complex dynamics in tobacco control communication. Their findings provide multidisciplinary insights for optimizing targeted intervention strategies, refining public service ad design, enhancing social media communication efficacy, and improving tobacco control policies, contributing to advancing precision and dynamism in tobacco control efforts amid evolving digital communication ecosystems.